2002
DOI: 10.1073/pnas.152085999
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of RGS8 gene determines inhibitory function of receptor type-specific Gq signaling

Abstract: The regulators of G protein signaling (RGS) proteins modulate heterotrimeric G protein signaling. RGS8 is a brain-specific RGS protein of 180 aa. Here we identified a short isoform of RGS8, RGS8S, that arises by alternative splicing. RGS8S cDNA encodes a N terminus of 7 aa instead of amino acids 1-9 of RGS8 and 10 -180 of RGS8. The subcellular distribution of RGS8 and RGS8S did not differ significantly in transfected cells. RGS8S accelerated, not as efficiently as RGS8, the turning on and off of Gi͞o-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…Our negative results for M 1 /M 3 mAChR selectivity of RGS2 reported here do not invalidate literature on receptor/RGS specificity (Zeng et al, 1998;Xu et al, 1999;Saitoh et al, 2002;Wang et al, 2002); rather, they suggest that mechanisms may be more complex than just receptor/RGS binding. It is clear that cell-type specific processes, such as scaffold molecules [i.e., G␣-interacting protein C terminus (GIPC)] may play a role.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Our negative results for M 1 /M 3 mAChR selectivity of RGS2 reported here do not invalidate literature on receptor/RGS specificity (Zeng et al, 1998;Xu et al, 1999;Saitoh et al, 2002;Wang et al, 2002); rather, they suggest that mechanisms may be more complex than just receptor/RGS binding. It is clear that cell-type specific processes, such as scaffold molecules [i.e., G␣-interacting protein C terminus (GIPC)] may play a role.…”
Section: Discussionsupporting
confidence: 53%
“…RGS2, -3, -4, -5, and -8 have been identified to inhibit G␣ q , yet relatively little is known about determinants of their function. There is substantial published evidence for receptor-dependent specificity of RGS proteins (Zeng et al, 1998;Xu et al, 1999;Saitoh et al, 2002;Wang et al, 2002), and direct binding of RGS2 and -4 to the i3 loop of G␣ q/11 -coupled mAChRs was recently demonstrated (Bernstein et al, 2004) with greater binding to the M 1 and M 5 i3 loops than for the M 3 i3 loop. However, association with full-length receptors and the functional significance of this interaction in cells was not investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been reported for different RGS proteins in regulating Gq proteins activated by distinct receptors (Xu et al, 1999); RGS3 and muscarinic m3 receptor; RGS5 and angiotensin AT1a receptor (Wang et al, 2002); RGS8 towards muscarinic m1 and substance P receptors (Saitoh et al, 2002); RGS-R4 subfamily and subtypes of muscarinic acetylcholine receptors (Roy et al, 2003;Bernstein et al, 2004). In the present study, we show that both RGSZ1 and RGSZ2 co-precipitate with m-opioid receptors, and that the association between RGSZ and Ga subunits is altered by a morphine challenge.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, the apparent selectivity of RGS19 as a GAP for MOR signaling and RGS4 as a GAP for DOR signaling is unexpected. However, there is accumulating evidence for GPCRs contributing to the specificity of RGS protein action (Xu et al, 1999;Saitoh et al, 2002;Wang et al, 2002Wang et al, , 2009Bernstein et al, 2004), and we (Wang et al, 2009) and others (Georgoussi et al, 2006;Xie et al, 2007) have suggested a role for the C-terminus of opioid receptors in providing specificity of RGS action at DOR versus MOR. Moroever, outside the RH domain, RGS19 has a more complex structure than RGS4 with an N-terminal cysteine string that binds to the N-terminal leucine-rich region of GAIP-interacting protein N-terminus (Fischer et al, Fig.…”
Section: Rgs19 Modulates M-opioid Receptor Signalingmentioning
confidence: 81%